Heavy ion beam probing – a tool to study geodesic acoustic modes and alfven eigenmodes in the T-10 tokamak and TJ-II stellarator - Melnikov, A.V.; Krupnik, L.I.; Barcala, J.M.; Bravo, A.; Chmyga, A.A.; Deshko, G.N.; Drabinskij, M.A.; Eliseev, L.G.; Hidalgo, C.; Khabanov, P.O.; Kharchev, N.K.; Komarov, A.D.; et al. (Вопросы атомной науки и техники, 2017)
Heavy ion beam probing (HIBP) is a unique diagnostic for core plasma potential. It operates in the T-10 tokamak and TJ-II flexible heliac. Multi-slits energy analyzers provide simultaneously the data on plasma potential φ (by beam extra energy), plasma density (by beam current) and Bpol (by beam toroidal shift) in 5 poloidally shifted sample volumes. Thus, the poloidal electric field and the electrostatic turbulent particle flux are derived. The fine focused (<1 cm) and intense (100 μA) beams provide the measurements in the wide density interval ne=(0.3...5)×10¹⁹ m⁻³, while the advanced control system for primary and secondary beams provides the measurements in the wide range of the plasma currents in T-10 and magnetic configurations in TJ-II, including Ohmic, ECR and NBI heated plasmas. Low-noise high-gain (10⁷ V/A) preamplifiers with 300 kHz bandwidth and 2 MHz sampling allow us to study quasi-coherent modes like Geodesic Acoustic Modes (GAMs) and Alfvén Eigenmodes (AEs). The spatial location, poloidal rotation velocity and mode numbers for GAMs and AEs were studied in the core plasmas. Зондирование пучком тяжёлых ионов (ЗПТИ) является уникальной диагностикой для исследования потенциала горячей плазмы, она работает на токамаке T-10 и стеллараторе TJ-II. Многощелевые анализаторы позволяют одновременно определять потенциал, плотность и полоидальное магнитное поле в пяти точках измерения в плазме, что позволяет найти полоидальное электрическое поле и турбулентный поток частиц. Хорошо сфокусированные (< 1 см) интенсивные (100 мкА) пучки позволяют вести измерения в широком интервале плотностей n‾e=(0.3...5)×10¹⁹ m⁻³, а система управления первичным и вторичным пучками обеспечивает измерения в пределах изменения параметров T-10 и TJ-II, включая режимы омического, электронно-циклотронного и инжекционного нагревов плазмы. Исследованы геодезические акустические моды и альфвеновские собственные моды частотой до 300 кГц. Зондування пучком важких іонів (ЗПВІ) є унікальна система діагностики для дослідження потенціалу в гарячій плазмі на токамаці Т-10 та стелараторі TJ-II. Аналізатори з багатою кількістю апертур дозволяють одночасно вимірювати потенціал, густину та полоїдальне магнітне поле у п’яти об’ємах плазми, що дозволяє знайти полоїдальне електричне поле та турбулентний потік часток. Гарно сфокусовані (< 1 см) інтенсивні (100 мкА) пучки дозволяють провести вимірювання в широкому інтервалі n‾e=(0.3...5)×10¹⁹ m⁻³ густини, а система керування первинним та вторинним пучками забезпечує вимірювання у межах діапазону зміни параметрів T-10 та TJ-II, які включають у себе режими омічного, електронно-циклотронного та інжекційного нагрівів плазми. Досліджено геодезичні акустичні моди і альфвенівські коливання особистої моди частотою до 300 кГц.